INTEREST RATE REGIME AND THE PERFORMANCE OF THE NIGERIAN CAPITAL MARKET - Jeroh, Edirin; Ekwueme, C. M. (Studies and Scientific Researches. Economics Edition, 2015)
This study x-ray’s the interest rates regime in Nigeria as it affects the performance of the Nigerian Capital Market. In order to achieve this objective, relevant data for a period of 33 years spanning from 1981 – 2013 were obtained from the Factbook of the Nigerian Stock Exchange, CBN Statistical Bulletin as well as the annual accounts of quoted firms for the relevant years. The data obtained were analysed with the Ordinary Least Square (OLS) technique. The result from our analysis reveal among others that changes in interest rate regimes have majorly influenced the level of the performance of the Nigerian Capital Market. Based on the above, we recommend that capital market regulators and other regulatory agencies should keep an eye on movements in interest rates and the Minimum Rediscount Rate (MRR) (now MPR) and watch their trend. We also recommend that efforts must be put in place to establish a policy review and reassessment mechanism that would help in assessing the impact of selected policy measures on the economy so that policy makers would know the effectiveness and efficiency of designed policies and be guided in the policy review and development process in the country.